Dynamics Of Migration In Islamic View - Sigit Danuansyah Mediawan S. (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Migration is an issue that has been going on for a long time in this part of the world, but not a few people view thatmigration is an act that threatens the domestic situation. Islam itself has migrated since the prophetic era which isoften known as Hijrah. This paper will discuss how the Islamic view of migration is often considered that it can bea threat to security and stability domestically in this era. This paper uses a qualitative descriptive method with thefindings that America is used as the mecca as a superpower has a different view of migration which can be a seriousthreat to the state, while Islam has another view, namely that migration or hijrah is a must if circumstances do notallow to settle in the country of origin.